2013
DOI: 10.5751/es-05665-180309
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Resilience: Teachings of Pikangikum First Nation Elders, Northwestern Ontario

Abstract: ABSTRACT. Although scholars of social-ecological resilience propose unity between humans and the natural world, much of this work remains based on Cartesian division of mind and body that denies it. We present an example of a unified system of resilience thinking shared with us by Anishinaabe (Ojibway) elders of Pikangikum First Nation, northwestern Ontario. The elders' views of boreal forest disturbance and renewal are distinct from western scientific approaches in their recognition of agency, the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
(29 reference statements)
0
27
0
1
Order By: Relevance
“…This is partially due to the fact that what must be obligatorily expressed in one language need not be obligatorily expressed in another, and thus the structure of the language can implicitly and explicitly affect how speakers engage with the world and influence memory, perception, and categorization (Markman and Hutchinson 1984, Harrison 2007, Deutscher 2010, Boroditsky 2011. Indigenous languages can provide refined and multifaceted descriptions of biodiversity (Hale et al 1992, Newmaster et al 2007), alternative ways of examining and relating to nonhuman animals (Ingold 2011, Miller andDavidson-Hunt 2013), and insight into the underlying processes that create biological structure and drive patterns of biodiversity (Ragupathy et al 2009, Gavin et al 2015.…”
Section: Figmentioning
confidence: 99%
“…This is partially due to the fact that what must be obligatorily expressed in one language need not be obligatorily expressed in another, and thus the structure of the language can implicitly and explicitly affect how speakers engage with the world and influence memory, perception, and categorization (Markman and Hutchinson 1984, Harrison 2007, Deutscher 2010, Boroditsky 2011. Indigenous languages can provide refined and multifaceted descriptions of biodiversity (Hale et al 1992, Newmaster et al 2007), alternative ways of examining and relating to nonhuman animals (Ingold 2011, Miller andDavidson-Hunt 2013), and insight into the underlying processes that create biological structure and drive patterns of biodiversity (Ragupathy et al 2009, Gavin et al 2015.…”
Section: Figmentioning
confidence: 99%
“…Social Framing: Making Sense of Collaboration and Conflict Understanding identities, issues, roles, and responsibilities is integral to understanding environmental governance systems that are inclusive of Indigenous Peoples (Corntassel, 2012;Miller & Davidson-Hunt, 2013). We use Kooiman's (2003) definition of governance as "the totality of interactions, in which public as well as private sectors participate, aimed at solving societal problems or creating societal opportunities" (p. 4).…”
Section: Research Approachmentioning
confidence: 99%
“…As Natcher et al (2005) contend, non-First Nations often demonstrate individualistic behaviour, valuing economics over the cultural consequences of forest resource development. Conversely, studies conducted in partnership with First Nations from across Canada have clearly demonstrated that Indigenous peoples throughout the country view themselves as partners in sacred relationships with the natural world, which must be maintained through respect, reciprocity and cultural protocols (e.g., Miller and Davidson-Hunt 2013). As a result of such differences in worldviews, each group will ultimately view acceptable harvesting practices in fundamentally different ways (Parsons and Prest 2003).…”
Section: Bridging Knowledge and Value Systemsmentioning
confidence: 99%
“…Miller and Davidson-Hunt (2013) for example, have acknowledged that the worldviews of Indigenous youth may vary considerably from older generations. Stevenson (2006) has echoed this insight, observing that the use of the term "conservation" is much more prevalent among Indigenous youth than it is among Elders.…”
Section: Broad Community Engagementmentioning
confidence: 99%